Cavity correlation and bridge functions at high density and near the critical point: a test of second-order Percus–Yevick theory. (1st September 2016) - Saeger, Austin R.; Johnson, J. Karl; Chapman, Walter G.; Henderson, Douglas
ABSTRACT: Cavity correlation functions, pair correlation functions, and bridge functions for the Lennard-Jones fluid are calculated from first Percus–Yevick (PY) theory and second-order Percus– Yevick (PY2) theory, molecular dynamics, and grand canonical Monte Carlo techniques. We find that the PY2 theory is significantly more accurate than the PY theory, especially at high density and near the critical point. The pair correlation function near the critical point has the expected slowly decaying long-range behaviour. However, we do not observe any long-range behaviour in the bridge function for the state points near the critical point we have simulated. However, we do note that the bridge function, which is usually negative near r = 0, becomes positive as r → 0. This behaviour is seen for the bridge functions computed from both PY2 and molecular dynamics, but not from PY. Abstract :